2015
DOI: 10.1167/iovs.15-17097
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Properties of Major White Matter Tracts in Strabismic Amblyopia

Abstract: PURPOSE. In order to better understand whether white matter structural deficits are present in strabismic amblyopia, we performed a survey of the tissue properties of 28 major white matter tracts using diffusion and quantitative magnetic resonance imaging approaches.METHODS. We used diffusion-based tensor modeling and a new quantitative T1 protocol to measure fractional anisotropy (FA), mean diffusivity (MD), and myelin-sensitive T1 values. We surveyed tracts in the occipital lobe, including the vertical occip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 66 publications
4
66
1
Order By: Relevance
“…4,7,8 The magnitude of the increase in mean diffusivity of the optic radiation was roughly consistent with our previous study (about 10% greater compared to controls). We previously suggested this finding provides cursory evidence of a feedback, rather than feedforward, model of cortical abnormality in amblyopia.…”
Section: Thalamocortical and Corticocortical White Matter In Amblyopiasupporting
confidence: 91%
See 2 more Smart Citations
“…4,7,8 The magnitude of the increase in mean diffusivity of the optic radiation was roughly consistent with our previous study (about 10% greater compared to controls). We previously suggested this finding provides cursory evidence of a feedback, rather than feedforward, model of cortical abnormality in amblyopia.…”
Section: Thalamocortical and Corticocortical White Matter In Amblyopiasupporting
confidence: 91%
“…This is not to suggest visual corticocortical white matter is unaffected per se in amblyopia, since similar recent studies have shown abnormalities in late-stream occipital projections such as the vertical occipital fasciculus, occipitofrontal projections such as the inferior longitudinal fasciculus, and interhemispheric connections in the anterior frontal corpus callosum. 8 Additionally, behavioral deficits such as difficulty inferring form from motion suggest amblyopia is associated with functional abnormalities more complex than can be explained by imbalanced binocular integration in thalamus and primary visual cortex. Without a more comprehensive cross-subject tractographic mapping of visual system white matter architecture, it is unclear the extent to which corticocortical pathway abnormalities reflect genuine differences versus overlap with voxels containing abnormal thalamocortical axons.…”
Section: Thalamocortical and Corticocortical White Matter In Amblyopiamentioning
confidence: 99%
See 1 more Smart Citation
“…1-2). We measured the white matter tissue along the OT and OR using tract profiles (Yeatman et al 2012;Ogawa et al 2014;Allen et al 2015;Ajina et al 2015;Duan et al 2015;Gomez et al 2015;Leong et al 2016;Libero et al 2016) and the tensor model (Basser and Jones 2002;Basser and Pierpaoli 1998). Supplementary Fig.…”
Section: Visual White Matter and Retinal Damagementioning
confidence: 99%
“…For example, the human white matter is affected during normal aging as well as in age-related diseases, such as Alzheimer's or progressive cognitive degeneration (Mayda et al 2010;Wang et al 2010Wang et al , 2012Yeatman et al 2014; Thomason and Thompson 2011). The visual white matter pathways have been also shown to be affected by visual and eye disease, for example, developmental prosopagnosia (Gomez et al 2015;Thomas et al 2008), amblyopia (Allen et al 2015(Allen et al , 2018Duan et al 2015), and retinal ganglion cell damage (Ogawa et al 2014) have all been reported to affect properties of the human white matter, please see Ariel Rokem et al 2017;Millington et al 2014 for reviews. Evidence from in vivo studies suggest that macular degeneration also affects volume of the human primary visual cortex and the visual pathways (Prins et al 2016a, b;Hernowo et al 2014;Malania et al 2017).…”
Section: Introductionmentioning
confidence: 99%